Mineralização de nitrogênio do esterco bovino e produção de alface em função de N-ureia - Sylvestre, Thiago de Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
An experiment in laboratory and three in the field were carried out with the objectives of compare laboratory and field methods to determine N mineralization rate of cattle manure; assess lettuce productivity and nitrate accumulation in plants, due to urea-N rates at planting and topdressing. The soil used in the laboratory experiment was collected at the site of field experiments and is an Oxisol. In the laboratory method, soil and manure (0, 5, 10, 20, 40 and 80 t ha-1) were incubated at 28ºC for 180 days, and the amount of N mineralized (NH4 +-N + NO3 --N) was determined periodically. Field experiment was carried out in polyethylene buried bags in beds, in 0.1 m deep, with the same doses of manure and the same evaluation times used in the laboratory, from November 2011 until May 2012. Simultaneously, a field experiment was carried out with lettuce, using the same doses of manure to get N uptake in 180 days (three successive crops). In the following year, in November and December, it was carried out an experiment combining two doses of nitrogen fertilizer at transplanting (0 and 40 kg ha-1 urea-N) and four in topdressing (0, 30, 60 and 90 kg ha-1), divided into two or three application times (2x4x2 factorial). In this experiment, the dose of manure was calculated based on the rate determined by buried bags method. The methods of incubation in the laboratory and in the field were not efficient for predicting N availability to lettuce in soil fertilized with cattle manure. The application of 40 kg ha-1 urea-N at transplantation resulted in increased productivity by 26% (3,583 kg ha-1) and 98% of maximum productivity was obtained with 60 kg ha-1 N, splitted in two applications. The nitrate content in plants was below the limit tolerated at all dose combinations at planting and topdressing

Foram conduzidos quatro experimentos, um no laboratório e três no campo, com os objetivos de: comparar métodos de determinação da mineralização de N de esterco bovino em laboratório e em campo; avaliar a produtividade de alface e o acúmulo de nitrato nas plantas, em função de doses de N-ureia no plantio e em cobertura. O solo utilizado no experimento em laboratório foi coletado no local dos experimentos em campo e é um Latossolo Vermelho. No ensaio em laboratório foi feita incubação de solo mais esterco (0, 5, 10, 20, 40 e 80 t ha-1), a 28oC, por até 180 dias, com avaliação periódica da quantidade de N mineralizado (N-NH4 + + N-NO3 -). Em campo, de novembro de 2011 a maio de 2012, foi conduzido experimento com sacos de polietileno enterrados em canteiros, a 10 cm de profundidade, com as mesmas doses de esterco e os mesmos tempos de avaliação usados no laboratório. Simultaneamente, em campo, foi conduzido experimento com alface, empregando as mesmas doses de esterco, para obter o N absorvido em 180 dias (três cultivos sucessivos). No ano seguinte, nos meses de novembro e dezembro, foi conduzido experimento em campo, combinando duas doses de adubo nitrogenado no transplantio (0 e 40 kg ha-1 de N-ureia) e quatro em cobertura (0, 30, 60 e 90 kg ha-1), parceladas em duas ou três vezes (fatorial 2x4x2). Neste experimento, a dose de esterco aplicada foi calculada com base na taxa de mineralização determinada com o método dos sacos enterrados. Os métodos de incubação em laboratório e em campo não foram eficientes para predizer a disponibilidade de N para alface em solo adubado com esterco bovino. A aplicação de 40 kg ha-1 de N-ureia no transplantio das mudas resultou em aumento de produtividade de 26% (3.583 kg ha-1) e 98% da produtividade máxima foi obtida com 60 kg ha-1 de N em cobertura, parcelados em duas aplicações. O teor de nitrato nas plantas ficou abaixo do limite tolerado em todas as combinações ...
Keywords: Alface; Adubação orgânica; Fertilizantes nitrogenados; Produtividade agrícola; Mineralogia do solo; Organic fertilizers